2016
DOI: 10.1108/mrr-01-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Research on customer switching behavior in the service industry

Abstract: Purpose This study aims to analyze and explain the characteristics and findings in previous studies of switching behavior and identifies the developments within this topic in order to improve its current understanding. Design/methodology/approach The authors construct a literature database of studies published in prominent business and management journals from 1996 to 2013 and conduct an analysis using the variables in the data fields. Furthermore, we execute meta-analysis to combine the research goals of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Because shoppers who possess a higher level of service experience conscientiousness than others may be more prone to service dissatisfaction, the finding, therefore, mirrors previous discussions about the role of customer dissatisfaction in customer switching behaviour (cf. Chuang and Tai 2016;Fan and Suh 2014). Moreover, as predicted and consistent with previous research (Osakwe and Chovancová 2015), this study finds that positive perceptions concerning online ad usefulness, in addition to service expectations, increasingly empower shoppers to use price comparison websites.…”
Section: Short Discussion and Conclusionsupporting
confidence: 88%
See 1 more Smart Citation
“…Because shoppers who possess a higher level of service experience conscientiousness than others may be more prone to service dissatisfaction, the finding, therefore, mirrors previous discussions about the role of customer dissatisfaction in customer switching behaviour (cf. Chuang and Tai 2016;Fan and Suh 2014). Moreover, as predicted and consistent with previous research (Osakwe and Chovancová 2015), this study finds that positive perceptions concerning online ad usefulness, in addition to service expectations, increasingly empower shoppers to use price comparison websites.…”
Section: Short Discussion and Conclusionsupporting
confidence: 88%
“…The reasons why customers engage in switching intentions and/or behaviour remains an important topic in the literature to this day (Bhattacherjee et al 2012;Fan and Suh 2014;Gopta et al 2004;Malhotra and Malhotra 2013;Mosavi et al 2018;Pourabedin et al 2016). Multiple reasons exist for this kind of behaviour (Chuang and Tai 2016;Keaveney 1995;Malhotra and Malhotra 2013;Mosavi et al 2018;Zhang et al 2012) but a factor often identified as a key determinant is the attractiveness of alternatives (Chuang and Tai 2016;Xu et al 2013;Zhang et al 2012). In the context of this study, consumers might easily switch between online stores when it is believed they can get better price deals elsewhere.…”
Section: Eswitching Behaviourmentioning
confidence: 99%
“…Bansal, et al [1], for their part, suggest that in the context of services, the pulling factors of the PPM framework are very much related to the attractiveness of the alternative. Chuang and Tai [21] are in the same line of proposing that the most important pull factors for switching behaviour in the context of services are specifically related to the attractiveness of the alternative service.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the PPM framework in the context of services, Bansal, et al [1] suggested that the poor quality of the current service, poor value, low confidence, poor commitment, and high price are the push factors. Chuang and Tai [21], in turn, present their own literature review of service exchange behaviour, citing that the factors associated with the enjoyment of the current service are the most important pushing factors affecting switching behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous switching channel and provider, these authors call cross-channel free-riding, which is prompted by the customers' perceived self-efficacy to use multiple channels. Customer switching behavior is most often presented in relation to change the supplier, in particular services provider basis on customer subscription or membership [3]. Chuang and Tai conclude that in the research on switching suppliers, satisfaction, switching cost and attractiveness of alternatives appear most often as a predictor of switching intention.…”
Section: Introductionmentioning
confidence: 99%